PENGARUH HUBUNGAN INTERPERSONAL DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING (STUDI PADA KPKNL YOGYAKARTA) - Hidayah, Afid Khatul; Subkhan, Muhammad (UNIKA Santo Thomas, 2025)
The following study aims to find the influence of interpersonal relationships and the work environment on employee performance by work motivation as an intervention variable at KPKNL Yogyakarta. Quantitative method with a population of 58 respondents. The sample was utilized through a saturated sample technique with SEM (Structural Equation Modeling) analysis. The research conclusions can be concluded that: (1) interpersonal relationships have an influence on employee performance (2) interpersonal relationships have an influence on work motivation (3) the work environment has no influence on employee performance (4) the work environment influences work motivation (5) work motivation has no influence on employee performance (6) work motivation is not proven as an intervening variable between the influence of interpersonal relationships on employee performance and (7) work motivation is not proven as an intervening variable between the influence of the work environment on employee performance.